Interactional Metadiscourse Markers in English Research Article Abstracts Written by Non-Native Authors: A Corpus-Based Contrastive Study - Boginskaya, Olga (Íkala, Revista de Lenguaje y Cultura, 2023)
Abstracts in research articles play a crucial role in settling the impact of academic articles. However, despite the abundance of research on academic discourse, variation in its linguistic features among scholars from different academic cultures seems to have remained untouched. This corpus linguistics study presents a comparative analysis of interactional metadiscourse markers in 96 research article abstracts written in English by both Russian and Spanish scholars in the field of linguistics. The study is based on the assumption that the distribution of interactional metadiscourse devices is different in the abstracts produced by each group of scholars. This is because Spanish academic discourse has been influenced by the growing expansion of Anglophone academic conventions to a larger extent. The theoretical basis of the study is Hyland’s (2005) taxonomy of interactional metadiscourse markers, which offers a pragmatically-grounded method for studying different types of such markers in academic discourse. Findings revealed that Spanish scholars leave more traces of themselves in their writing and take far more explicitly involved positions than Russian scholars. These findings carry pedagogical implications for academic writing course designers and instructors and can enhance non-native English writers’ knowledge of culture-specific and international academic writing conventions in the discipline.